Expert Knowledge Elicitation to assess the ability of matrices to transmit African swine fever virus. Issue 12 (23rd December 2021) - ,; Mosbach‐Schulz, Olaf; Christoph, Eugen; Gervelmeyer, Andrea
Abstract: An Expert Knowledge Elicitation (EKE) was carried out regarding the possible contamination with African swine fever virus (ASFV) of products used as pig feed, their traded/imported volumes and their use on pig farms. In addition, the EKE also concerned empty vehicles returning to ASF‐unaffected areas of the EU after delivering pigs to ASF‐affected areas. The EKE was carried out by three independent groups of six to eight experts each. It was carried out in three steps: assessing the likelihood of contamination of a product at origin; assessing the likelihood of the contaminated product having enough viable virus to infect a pig (the infectious dose); and assessing the volume of trade or imports of each product from an affected area in either the EU or Eurasia which would be delivered to either a small‐scale or large‐scale pig farm. This report presents the results of the three elicitations. The results of the EKE have been used by the AHAW Panel in a pathway model to determine the likelihood of each product to introduce ASFV into non‐affected areas of the EU based on relative risk ranking.